The Threat of Multi‐Year Drought in Western Amazonia. Issue 9 (3rd September 2018) - Parsons, L. A.; LeRoy, S.; Overpeck, J. T.; Bush, M.; Cárdenes‐Sandí, G.M.; Saleska, S.
Abstract: Recent "once‐in‐a‐century" Amazonian droughts highlight the impacts of drought and climate change on this region's vegetation, carbon storage, water cycling, biodiversity, land use, and economy. The latest climate model simulations suggest this region will experience worsening future drought. However, the instrumental record is too short to quantify the range of background drought variability, or to evaluate extended drought risk in climate models. To overcome these limitations, we generated a new, highly resolved lake record of hydroclimatic variability within the western Amazon Basin. We find that Amazonia has regularly experienced multi‐year droughts over the last millennium. Our results indicate that current climate model simulations likely underestimate the background risk of multi‐year Amazonian drought. These findings illustrate that the future sustainability of the Amazonian forest and its many services may require management strategies that consider the likelihood of multi‐year droughts superimposed on a continued warming trend. Plain Language Summary: The Amazon basin recently experienced multiple "once‐in‐a‐century" droughts that impacted the region's water cycle, economy, vegetation, and carbon storage. However, the instrumental record in this region tends to be too short to determine if these droughts are abnormal in a long‐term context. Paleoclimate data can extend drought records that help water and land managers plan for these events in the face of climate change. To provide additional information about pre‐instrumental drought, here we present results from a new paleoclimate lake record based on sediments we recovered from Lake Limón in the Peruvian Amazon. We find that concentrations of elements in the Lake Limón sediment cores are likely recording past changes in rainfall variability. We use this elemental variability to generate a new, millennial‐length record of drought for the western Amazon. We show that this region has experienced multi‐year droughts at least twice a century over the last ∼1, 400 years. The frequency and severity of these paleoclimate‐inferred droughts may exceed most climate model and instrumental‐era drought risk estimates. Our findings illustrate that the future sustainability of the Amazonian forest and its many ecosystem services may require management strategies that consider the likelihood of multi‐year droughts in addition to continued warming. Key Points: We present results from a high‐resolution paleoclimate record of hydroclimatic variability in western Amazonia Our paleoclimate record suggests western Amazonia has regularly experienced multi‐year drought over the last millennium Earth system model simulations may underestimate the background risk of multi‐year western Amazonian drought